Viabilitas Benih Pala (Myristica fragrans HOUTT) pada Beberapa Tingkat Skarifikasi dan Konsentrasi Air Kelapa Muda - Erida Nurahmi; Agam Ihsan Hereri; Afriansyah Afriansyah (Fakultas Pertanian, Universitas Syiah Kuala, 2010)
Nutmegg Seed (Myristica fragrans HOUTT) Viability Scarification on Several Levels and The Concentration of Young Coconut Water.ABSTRACT. One of the efforts to eliminate the mechanical barrier is by scarification treatment (scrubbing) the seed that becomes a thin shell that easily enter the water and air. Besides the presence of growth regulators in seed also be an important factor for accelerating the growth of seedlings. The experimental design used in this research in Completely randomized design (CRD) 3x3 factorial with three replications. There are two factors studied, namely scarification percentage and the concentration of young coconut water. Increased nutmeg seed viability and seedling vigor due scarification treatment , except for potential growth. Scarification 100% gives the acceleration of growth was significantly different from the seed without scarification but not significantly different from the scarification 50%. Concentration of 100% coconut water could also accelerate the growth of normal seeds without significantly as compared with young coconut water immersion, but not significantly different from the concentration or 50% young coconut water. There were no significant interaction between treatments were tested on the viability and vigor of seed germinating of nutmeg.